ANALISIS PENDIDIKAN ORANG TUA TERHADAP KELUARGA DALAM AL-QUR’AN SURAH AT-TAHRIM AYAT 6 KAJIAN TAFSIR AL-MISBAH KARYA M.QURAISH SHIHAB - Hertoyo, Muhammad; Robiah, Robiah (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research was motivated by various family problems that were most public among the community. Parents who lack attention in educating the family so that there are many problems in the household (broken home). The purpose of this study is to find out how the concept of parental  education to the family in Surah At-tahrim Verse 6 Tafsir Al-Misbah by M.Quraish Shihab and also to find out the relevance to education in today's era. Literature research (Libreray Research) is a literature review that takes written data from various literature contained in the library. This research was conducted using data collection techniques by searching for information, reviewing books, journals related to this title. The results of this study obtained that the conclusion that there are several concepts of education for parents to the family contained in Surah At-tahrim Verse 6 Tafsir Al-Misbah by M.Quraish Shihab,  namely: education starts from home and its redaction to both parents. While the relevance of parental education to the family in the interpretation of Al-Misbah has been running in the current era, so as to create a generation of ethics and noble morals.